Detroit Area Study, 1995: Social Influence on Health: Stress, Racism, and Health Protective Resources - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 2002)
This survey explored the ways in which social influences, such as stress and racism, affected health, and the impact these influences had on the respondents' outlook on life. Respondents were questioned about their health status and their exercise, smoking, sleeping, and dieting habits, as well as about diagnosed health problems and depression and their effects on daily activities. Respondents were also asked a series of questions regarding their employment status, type of job and whether it was a supervisory position, the racial makeup of their workgroup, their perceptions of their position and job, the likelihood of their finding another job, hassles experienced while at work, and whether they had any trouble balancing family and work. Another series of questions asked respondents whether they had been a victim of a serious physical attack or assault, robbery, or home burglary, if they had ever been unfairly searched, stopped, or questioned by police, why they felt they had been treated this way, and if they felt they had ever been treated unfairly by a teacher, landlord, or neighbor. Opinions were also solicited on the respondents' experience with depression and anxiety. Respondents were asked whether they felt it was possible to reach their goals, how satisfied they were with their present situation, how often they felt depressed and how long this feeling lasted, whether they lost weight or sleep due to this feeling, how this feeling of depression made them view themselves, how often and how long they were worried about things that were not likely to happen, how often they worried about non-serious things, and how they felt physically when they were anxious or depressed. Another set of questions queried respondents on alcohol and drug use. Respondents were asked how often they drank alcohol, the most they had to drink at one time, whether they had experienced any addiction to alcohol or experienced any emotional or psychological problems associated with drinking, whether they had any problem controlling their drinking, whether they had used drugs outside of a doctor's order, what types of drugs they had used, how often and in what type of situations they had used these drugs, and whether they had any addiction to the drugs. Respondents were also asked whether they had a regular doctor, whether they went to a doctor's office or clinic to seek medical attention, the last time they had gone for a checkup, how they were treated by staff at the visit, whether they trusted their doctor, the reasons why they did or did not receive medical attention, and whether they had health insurance. Respondents were also asked for their perceptions of differences between Blacks and whites, attitudes toward affirmative action with regard to employment, and their attitude toward interracial relationships. Another battery of questions queried respondents on any fears or phobias they had, such as a fear of animals, water, or visiting a doctor or dentist. Questions focused on the severity of these fears, how long they had had these fears, and how much these fears interfered in daily activities. A final set of questions gathered demographic information on respondents such as highest level of education completed, political affiliation, religious affiliation, level of religious participation, importance of religion, birth date, whether they owned their own home or rented, how much they spent on food each week, total family income for the year 1994, and the height and weight of respondents.